Navigating Indonesian Educational Frontiers: The Hidden Curriculum Crafters of English Instructions - Mustofa, Mutmainnah; Hairi, Sohibul; Elga Romadhon, M Galuh (LETS: Journal of Linguistics and English Teaching Studies, 2025)
This research project intends to engage with the perspectives of ’shadow teachers’ who perform private tutoring sessions in Indonesia, focusing on a gap in the literature concerning the construction and execution of English learning programs within informal education settings. Existing studies have explored individualized instruction within formal classroom contexts. However, scant attention has been directed towards the role of shadow teachers with regard to curriculum development beyond the conventional school system. This study hopes to address some of these gaps by drawing upon the practical wisdom of these educators to reveal the complexities, collaborations, and tailored English Language learning program designing as well as the bespoke decision-making processes which occur within non-standardized educational settings.